Religions and Trade Religious Formation, Transformation and Cross-Cultural Exchange between East and West - Wick, Peter; Rabens, Volker (Dynamics in the History of Religions, 2013)
Religions and Trade carves new pathways into the world of religious dynamics. In this array of essays a number of international scholars investigate the ways in which eastern and western religions were formed and transformed from the perspective of "trade."; Readership: All people interested in the formation of religion and interreligious dynamics, and anyone concerned with cross-cultural exchange between east and west.